Assessing renal function in children with hydronephrosis - additional feature of MR urography - Hadjidekov, George (Radiology and oncology (Ljubljana), 2011)
Background. Magnetic resonance urography (MRU) is one of the most attractive imaging modalities in paediatric urology, providing largest diagnostic information in a single protocol. Therefore, the aim of our study was to assess the diagnostic value of MRU in children with urogenital anomalies (especially anomalies of the renal pelvis and ureter) and the renal function using different post-processing functional software. Patients and methods. Ninety six children (7 days - 18 years old) were examined. In 54 patients of them, a static T2 MRU was completed by excretory T1 MRU after gadolinium administration and functional analysis has been performed using two functionalanalysis softwares ĆCHOP-fMRUĆ and ĆImageJĆ software. Results. MRU showed suspicious renal and the whole urinary tract anomalies with excellent image quality in all children. In ureteropelvic obstruction, MRU was confirmatory to the other imaging techniques, but it was superior modality concerning the evaluation of end-ureteral anomalies. There was an excellent correlation between the MRU data and diagnosis, determined by surgery. The renal transit times, renal volumes and volumetric differential renal function were assessed separately by ĆCHOP-fMRUĆ and ĆImageJĆ with excellent agreement with 99mTc-DTPA and among them.Conclusions. MRU overcomes a lot of limitationsof conventional imaging modalities and has a potential to become a leading modality in paediatric uroradiology. Synthesis of both anatomical and functional criteria in MR urography enables to select the best candidates for surgical treatment. Even small kidney dysfunction can be detected by functional analysis software.
Keywords: Abnormalities; Child; Diagnosis; Hidronefroza; Hydronephrosis; Kidney; Kidney Function Tests; Ledvica; Ledvični funkcijski testi; Magnetic Resonance Imaging; Magnetna resonanca; Otrok; Retrospective Studies; Retrospektivne študije; Urografija; Urography